The effects of University environments, personal traits and risk taking towards entrepreneurial intention among undergraduate students / Jaslin Md Dahlan ... [et al.] - Md Dahlan, Jaslin; Zainuddin, Noor Azrin; Mat Din, Syaidatul Zarina; Md Salleh, Siti Aishah (UiTM Cawangan Johor, 2019)
The unemployment rate has increased over the years. Due to that, the government has regards entrepreneurship as a better employment alternative for graduates after finishing their study. Although there are many factors that can affect the undergraduates in determining their entrepreneurial intention. Therefore, this study was carried out to determine the factors affecting entrepreneurial intention among the undergraduate student in the UiTM Segamat. This survey used a quantitative method in order to collect the data using a questionnaire, where 191 respondents were involved in this research. There are four main variables have been adopted from past research which is: entrepreneurial intention, university environment, risk-taking and personality traits (innovation, sociability, planning, and leadership). According to the result, only two variables namely sociability and risk-taking were the significant factors affecting entrepreneurial intention among UiTM Johor students, whereby Risk Taking (p=0.000) and sociability (p=0.008). The finding of this result would provide a useful insight into the education institution for identifies the factors that can affect and boost the student entrepreneurial intention.